1995
DOI: 10.1007/bf00593711
|View full text |Cite
|
Sign up to set email alerts
|

Serial MRI in early Creutzfeldt-Jacob disease with a point mutation of prion protein at codon 180

Abstract: We report a 66-year-old woman with histologically diagnosed Creutzfeldt-Jacob disease (CJD), followed with MRI from an early clinical stage. MRI demonstrated expansion of the high cortical signal on T2-weighted images, which differs from previous MRI reports of CJD. This patient followed an atypical clinical course: 16 months had passed before she developed akinetic mutism, and periodic sharp waves had not been detected on EEG after 2 years in spite of her akinetic mutism. Brain biopsy showed primary spongifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Our results, along with the previous reports of fCJD, also suggest that the imaging findings in fCJD are in general similar to those seen in sCJD. 5,15,17,[19][20][21][22]33,34 These results are consistent with fCJD having clinical and neuropathologic features seen in the most common molecular subtype of sCJD, which is the MM1 subtype. 14 The basal ganglia signal intensity changes are important markers for CJD.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our results, along with the previous reports of fCJD, also suggest that the imaging findings in fCJD are in general similar to those seen in sCJD. 5,15,17,[19][20][21][22]33,34 These results are consistent with fCJD having clinical and neuropathologic features seen in the most common molecular subtype of sCJD, which is the MM1 subtype. 14 The basal ganglia signal intensity changes are important markers for CJD.…”
Section: Discussionsupporting
confidence: 72%
“…[15][16][17][18][19] A collaborative surveillance project of genetic prion cases indicated that approximately 50% of a small number (not specified) of patients with fCJD due to the E200K mutation had abnormal MR images, but specific imaging results were not described. 33 There are also larger imaging studies focused on sCJD that combined a few fCJD patients with sCJD patients into a single subject group but report the MR findings of the combined sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No kuru or amyloid plaques were detected in the central nervous system. These findings were consistent with pathological changes reported in cases with CJD with a codon 180 mutation [3,4,6] . Immunoblot analysis of prion protein could not be performed due to technical problems.…”
Section: Case Reportsupporting
confidence: 81%
“…In most cases occurrence is sporadic, but a small proportion of cases are familial. Among various associated mutations of the prion protein (PrP) gene identified by genetic analyses, a point mutation at codon 180 has been confirmed in only 7 patients, who characteristically showed a relatively long survival, old-age onset, absence of periodic synchronous discharges on electroencephalography (EEG) and lack of affected family members [3][4][5][6][7][8] . We report another CJD case with the same mutation of PrP, where neuroradiologic findings showed an unexpected and possibly informative dissociation.…”
Section: Case Reportmentioning
confidence: 99%